Analisis Tanggung Jawab Hukum Penyelenggara Jasa Telekomunikasi Terhadap Kerahasiaan Data Call Record Pengguna Layanan: Perspektif Hukum Telekomunikasi - Meliana, Yang (Lex Librum : Jurnal Ilmu Hukum, 2024)
Protection of personal data, including call records, is one of the important aspects that telecommunications service providers must pay attention to. Law Number 36 of 1999 concerning Telecommunications and its implementing regulations stipulate the obligation of telecommunications service providers to ensure the confidentiality of user data. However, a number of data breach cases have still been found, raising concerns about the effectiveness of the existing regulations. The normative legal method is used in this research. The analysis results indicate that although regulations are in place, the main challenge in protecting call record data lies in the implementation of oversight and law enforcement, which has not yet been optimal. This research recommends strengthening regulations and oversight to enhance the accountability of telecommunications service providers in safeguarding user data confidentiality.